Political Risk : The Missing Link in Understanding Investment Climate Reform? - Dreyhaupt, Stephan (World Bank, Washington, DC, 2012)
Political risk has once again become a key concern of investors after the perceived openness and liberalization of foreign direct investment (FDI) regimes in the 1990s. Governments that do not recognize this trend pay a high price in lost investments. Confronting political and regulatory risks as part of the investment climate is thus crucial for countries to make their business environments more competitive. This note suggests reforms that can have immediate impacts: addressing ex ante and ex post issues in the legal and regulatory framework to protect investors, mitigating risks at the sector level, managing reputational and integrity risks at the project level, and using financial instruments to ease short-term impediments in the investment climate.